Asymmetric electroresistance of cluster glass state in manganites - Lourembam, James (2014)
We report the electrostatic modulation of transport in strained Pr0.65(Ca0.75Sr0.25)0.35MnO3 thin films grown on SrTiO3 by gating with ionic liquid in electric double layer transistors (EDLT). In such manganite films with strong phase separation, a cluster glass magnetic state emerges at low temperatures with a spin freezing temperature of about 99 K, which is accompanied by the reentrant insulating state with high resistance below 30 K. In the EDLT, we observe bipolar and asymmetric modulation of the channel resistance, as well as an enhanced electroresistance up to 200% at positive gate bias. Our results provide insights on the carrier-density-dependent correlated electron physics of cluster glass systems.